Developing and validating a scale for non-academic staff’s service competencies in higher education - Phan Thi Nga; Amjad Shamim; Rohani Salleh (Cogent Education)
Though scholars have given significant attention to research on service quality in higher education, there is limited research exploring the contribution of non-academic staff to enhancing service quality at higher education institutions. One reason for the lack of empirical research on this topic is the absence of a measurement scale for the service competencies of non-academic staff (NONACA-SERCOM) in higher education institutions. Therefore, this study aims to develop and validate a multidimensional scale to measure essential service competencies for university support staff. Following a rigorous and thorough standard scale development procedure, this study developed and validated NONACA-SERCOM as a higher-order construct with three dimensions: interpersonal, self-management and professional competencies. The final 13-item NONACA-SERCOM multidimensional scale contributes to the body of research on higher education by looking at the service competencies of university support staff. It lays the groundwork for future studies examining how non-academic staff’s service competencies influence service quality and other aspects in higher education institutions.